Evaluation of Hydrodynamic Closures for Bubbly Regime CFD Simulations in Developing Pipe Flow. Issue 8 (23rd May 2019) - Shiea, Mohsen; Buffo, Antonio; Baglietto, Emilio; Lucas, Dirk; Vanni, Marco; Marchisio, Daniele
Abstract: The effect of interfacial forces and relevant closures, particularly the lift and wall lubrication forces, on the predictions of Eulerian‐Eulerian computational fluid dynamics simulations of bubbly flows was studied. The test case under study was a developing turbulent bubbly pipe flow, simulated by using OpenFOAM. The results show that the geometric approach to consider the wall effect leads to better agreement than a standard relation assuming asymmetric drainage around the bubble near the wall. Furthermore, the results verify the need for employing negative lift coefficients in cases with large bubbles. A sensitivity analysis on the lift coefficient highlighted the importance of investigating spatially developing flows to draw general conclusions on the applicability of closure relations. Abstract : Predictions of Eulerian‐Eulerian multiphase computational fluid dynamics simulations of bubbly flows depend strongly on the choice of closures for interfacial forces, i.e., drag, turbulent dispersion, lift, and wall lubrication. This work studies the effect of interfacial forces, particularly the lift and wall lubrication forces, by simulating a developing turbulent bubbly pipe flow.